Personal data nanagement with the Databox: what’s inside the box? - Mortier, Richard; Zhao, Jianxin; Crowcroft, Jon; Wang, Liang; Qi, Li; Haddadi, Hamed; Amar, Yousef; Crabtree, Andy; Colley, James; Lodge, Tom; Brown, Anthony; McAuley, Derek; et al. (2016)
We are all increasingly the subjects of data collection and processing systems that use data generated both about and by us to provide and optimise a wide range of services. Means for others to collect and process data that concerns each of us – often referred to possessively as “your data” – are only increasing with the long-heralded advent of the In- ternet of Things just the latest example. As a result, means to enable personal data management is generally recognised as a pressing societal issue. We have previously proposed that one such means might be realised by the Databox, a collection of physical and cloud- hosted software components that provide for an individual data subject to manage, log and audit access to their data by other parties. In this paper we elaborate on this proposal, describing the software architecture we are developing, and the current status of a prototype implementation. We con- clude with a brief discussion of Databox’s limitations.